Export efficiency and determinants of Indonesian spices exports to major destination countries - Maya Aulia Ardini; Fahmi Salam Ahmad; Syarifah Amaliah (Optimum: Jurnal Ekonomi dan Pembangunan, 2026)
Indonesian spice exports (HS 0904 to 0910) have been a major contributor to non-oil and gas exports. One issue related to spice exports is that their performance often fluctuates and does not truly reflect the "full potential" that can actually be achieved. Therefore, this study seeks to answer two questions: how efficient Indonesian spice exports are and what factors most determine their performance in eleven key destination markets from 2012 to 2023. The method used is the Stochastic Frontier Gravity Model (SFGM), which estimates the influence of economic factors and sources of inefficiency within a single framework. With this analytical method, export performance is not only assessed based on actual figures but also directly compared with their maximum potential. Based on the estimation results, Indonesia's real GDP, the real exchange rate, and economic distance are negatively related to spice exports. Conversely, partner country GDP and government effectiveness in destination countries have a positive and significant impact. The efficiency estimate shows a moderate figure, with an average of only 54.17%. Among the partner countries studied, India was the most efficient market (88.20%), while Japan ranked lowest (5.39%). The Covid-19 dummy factor did not prove statistically significant. Overall, these findings indicate wide differences in efficiency across destination countries. Therefore, future strategies should not simply focus on increasing export volumes but also focus on improving efficiency, strengthening logistics competitiveness, and expanding export destinations to maximize Indonesia's spice export performance.